A quality by design approach with comprehensive green analytical chemistry assessment: Development, validation, and application of a high-performance liquid chromatographic method for quantifying meropenem trihydrate in nanosponges and marketed formulations - Ashwini T, Sanjay Garg, Padmaja A. Shenoy, Raghu Chandrashekhar, Yogendra Nayak, Usha Y. Nayak (Journal of Applied Pharmaceutical Science, 2025)
Meropenem trihydrate (MPN), pivotal in antimicrobial therapeutics, necessitates accurate analytical methods for its quantification across pharmaceutical formulations. The research aimed to develop a Quality by Design (QbD)-driven high-performance liquid chromatography (HPLC) method and validate it for the quantification of MPN in traditional and novel formulations, with a focus on environmental sustainability. The study employed a QbD approach to develop an HPLC method, ensuring its robustness and adaptability. The method’s universality was evaluated in both traditional powders for injection formulation and a novel beta-cyclodextrin nanosponges formulation. Rigorous validation was conducted per the International Conference on Harmonisation Q2 (R1) guidelines, including extensive stability and degradation studies to ascertain the method’s tenacity under multifarious conditions. The QbD-driven HPLC method showcased impeccable precision and accuracy, with a recovery rate of 99% for the marketed product and an encapsulation efficiency of 88.7% for nanosponges. Furthermore, seven different green analytical chemistry tools were used, and they indicated a significant reduction in environmental impact compared to pre-existing methodologies. In conclusion, our QbD-driven HPLC method for MPN quantification melds technical prowess with environmental responsibility, signifying a noteworthy stride in pharmaceutical research. The method’s high precision and stability assessment provide clinicians with a reliable tool for ensuring accurate dosing in critically ill patients, ultimately enhancing therapeutic efficacy and reducing treatment failure risks. Furthermore, the method supports sustainable drug analysis, minimizing ecological hazards associated with pharmaceutical waste. The method’s adaptability and greenness set a benchmark for future analytical methodologies, emphasizing analytical rigor, and ecological conscientiousness.
Keywords: High-performance liquid chromatographic method, meropenem trihydrate, quality by design, nanosponge formulation, green analytical chemistry